2022
DOI: 10.3389/fnut.2022.979624
|View full text |Cite
|
Sign up to set email alerts
|

Sucralose consumption ameliorates high-fat diet-induced glucose intolerance and liver weight gain in mice

Abstract: Sucralose is one of the most widely used artificial sweeteners used by the food industry to reduce the calorie density of their products. Although broadly regarded as innocuous, studies show contrasting results depending on whether the research subjects are lean or overweight. In this study, we studied the effect of sucralose consumption on glucose homeostasis in a model of obesity. Male C57BL/6J mice were fed ad libitum with control or a high-fat diet (HFD) and drank either water or sucralose (0.1 mg/mL) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…After one week of adaptive feeding, animals were distributed randomly into three groups of ten mice each (Fig. 1): (1) CON group: fed with the AIN-93G diet and distilled water, (2) S-HSD group: fed with the HSD diet and 0.1 mg mL −1 sucralose solution (S-HSD), which is roughly equivalent to the FAO/ WHO-approved acceptable daily intake (ADI) in humans (∼15 mg per kg per day), 32 and (3) S-APE group: fed with the same diet as the S-HSD group, and gavaged with 500 mg per (kg bw day) APE. The APE solution was diluted to 0.1 mL per 10 g bw using aseptic water before gavaging.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…After one week of adaptive feeding, animals were distributed randomly into three groups of ten mice each (Fig. 1): (1) CON group: fed with the AIN-93G diet and distilled water, (2) S-HSD group: fed with the HSD diet and 0.1 mg mL −1 sucralose solution (S-HSD), which is roughly equivalent to the FAO/ WHO-approved acceptable daily intake (ADI) in humans (∼15 mg per kg per day), 32 and (3) S-APE group: fed with the same diet as the S-HSD group, and gavaged with 500 mg per (kg bw day) APE. The APE solution was diluted to 0.1 mL per 10 g bw using aseptic water before gavaging.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…Studies have demonstrated that sucralose intake can influence the activity and expression of these enzymes, thereby impacting lipid metabolism. For instance, research on mice fed a high-fat diet has shown that sucralose supplementation reduces glucose intolerance and improves gluconeogenesis, indicating its potential role in ameliorating metabolic dysregulation associated with obesity and insulin resistance ( 71 ). The Pathway between Sucralose and elevated uric acid levels, fat, triglycerides, and insulin may be mediated by metabolic syndrome, hypertension, and obesity as illustrated in Figure 1 , respectively.…”
Section: Sucralose Consumption and Its Association With Obesitymentioning
confidence: 99%
“… 66 68 While some studies have mentioned a weight-loss effect of artificial sweeteners, there is also contrary evidence that aspartame treatment induces abdominal adiposity in rats. 61 When consumed with a HFD, sucralose is observed by Pino-Seguel et al 69 to prevent weight gain and alleviate glucose intolerance in mice. Contrast results were detected by Wu et al 70 under a similar protocol wherein sucralose not only had no effect on the body weight of HFD-fed mice but also exacerbated HFD-induced fatty liver.…”
Section: Sweeteners and Nafldmentioning
confidence: 99%